Online consumer behavior : theory and research in social media, advertising, and e-tail - Close, Angeline, ....- (New York : Routledge, 2012)
Social media (e.g., Facebook, LinkedIn, Groupon, Twitter) have changed the way consumers and advertisers behave. It is crucial to understand how consumers think, feel and act regarding social media, online advertising, and online shopping. Business practitioners, students and marketers are trying to understand online consumer experiences that help instill brand loyalty. This book is one of the first to present scholarly theory and research to help explain and predict online consumer behavior.
Includes bibliographical references and index.
Keywords: Consumentengedrag; Consumer behavior; Electronic commerce -- Psychological aspects; Internet marketing; Marketing -- Sociale media; Online marketing